Economic warfare : are we vulnerable? / Farah Zamira Farush Khan and Anitawati Mohd Lokman - Farush Khan, Farah Zamira; Mohd Lokman, Anitawati (CMIWS and UiTM Press, 2014)
Previous research had shown how economic and financial warfare tools, such as sanctions and trade were used at international level in order to achieve a political goal of a certain country or a group of countries. However, there were very few in-depth studies done on the vulnerability of Malaysian economy to economic warfare and its potential impact on the decisions made by our government. It is therefore the aim of this study to determine the degree of vulnerability in Malaysian economy and various tools that could be used by other countries to launch an economic warfare against Malaysia.